2020
DOI: 10.1039/d0ra06596j
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ag-modified TiO2/ZnO heterojunction nanotree arrays with superior photocatalytic and photoelectrochemical properties

Abstract: The work involves the preparation of TiO2/ZnO heterojunction nanotree arrays by a three-step: hydrothermal, sol–gel, and secondary hydrothermal method, and then modification of Ag quantum dots (QDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Since Fujishima and Honda discovered that titanium dioxide (TiO 2 ) could photodecompose water to produce hydrogen in the 1970s [ 1 ], TiO 2 , as a traditional semiconductor material, has been widely utilized in the fields of photocatalytic degradation of pollutants, dye-sensitized solar cells, lithium-ion batteries, gas sensors, etc., due to its relatively good chemical stability, low cost, non-toxicity, and environmentally friendly nature [ 2 , 3 , 4 ]. However, TiO 2 is subject to many limitations in industrial application due to its relatively large bandgap (anatase: ~3.2 eV, rutile: ~3.0 eV) and the relatively rapid recombination rate of photogenerated electrons and holes [ 5 , 6 ]. Recent studies have shown that changing the crystal phase, grain size, morphology, specific surface area, heterogeneous structure, and exposed facets of TiO 2 is an effective way to increase the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Since Fujishima and Honda discovered that titanium dioxide (TiO 2 ) could photodecompose water to produce hydrogen in the 1970s [ 1 ], TiO 2 , as a traditional semiconductor material, has been widely utilized in the fields of photocatalytic degradation of pollutants, dye-sensitized solar cells, lithium-ion batteries, gas sensors, etc., due to its relatively good chemical stability, low cost, non-toxicity, and environmentally friendly nature [ 2 , 3 , 4 ]. However, TiO 2 is subject to many limitations in industrial application due to its relatively large bandgap (anatase: ~3.2 eV, rutile: ~3.0 eV) and the relatively rapid recombination rate of photogenerated electrons and holes [ 5 , 6 ]. Recent studies have shown that changing the crystal phase, grain size, morphology, specific surface area, heterogeneous structure, and exposed facets of TiO 2 is an effective way to increase the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the noble metals, silver (Ag) is an attractive metal due to its strong surface plasmon resonance (SPR) effect along with extraordinary physicochemical properties and less expensive compared to gold, palladium, and platinum. 32,33 Various studies of Ag-TiO 2 composites for efficient PEC water splitting have been demonstrated; [34][35][36][37][38][39] for instance, Peng et al successfully decorated the plasmonic Ag NPs on TiO 2 nanowires for the enhancement of PEC water splitting performance, 32 and Hou et al reported TiO 2 nanotube arrays coupled with Ag NPs, exhibiting impressive PEC water splitting activities. 40 A comparative table summary of recent studies for Ag/TiO 2 photoanodes is shown in ESI Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, an environmentally benign, economical, and facile technique to synthesize Ag-deposited TiO 2 nanoplates (Ag/TiO 2 NP) as a photoanode was reported, by the combination of a hydrothermal method and an electrodeposition technique. The Ag NP deposition can be achieved by several methods such as electrodeposition, 34,37,41 photodeposition, 35,36,42 and chemical reduction. [43][44][45] Among various techniques, electrodeposition has arisen as a promising technique for fabricating photoelectrodes due to its relative simplicity, low cost, and good dispersion, and improves interfacial deposition between the deposited layer and supporting electrode substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of pure ZnO in photocatalysis under visible and solar light is restricted due to its wide band gap and quick recombination of electron-hole pairs [6,7]. To solve these drawbacks, many researchers developed various methods, such as metal and nonmetal doping [8][9][10][11], coupling with other narrow-band gap semiconductors [12][13][14] and dye-sensitized semiconductors [15][16][17][18][19][20]. The use of dye molecules to sensitize ZnO particles is considered to be an effective way to expand light absorption into the visible region while also improving their photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%